Metasurface based symmetry transformation for single-shot angular momentum detection within a large mode space - Luo, Yixiong; Zhang, Runzhe; Guo, Yinghui; Pu, Mingbo; Li, Xiaoyin; Zhang, Qi; Zhang, Fei; Xu, Mingfeng; Zhou, Rui; Zhao, Zeyu; Luo, Xiangang (Frontiers in Physics, 2023)
The spin angular momentum (SAM) and orbital angular momentum (OAM) are unique properties of vortex beams and widely used in optical communication and sensing, wherein unambiguous detection of them is of significance. However, the existing methodologies mostly require complicated optical setups, bulky devices, multiple measurements and suffer from limited detection range and ability. Here, we propose a novel angular momentum (AM) detection mechanism that based on optical symmetry transformation for single-shot AM detection within a large mode space. We first give a detailed theoretical derivation and then carry numerical verification. Subsequently, an ultracompact metasurface is designed so that an OAM mode high up to 150 orders can be determined with a single-shot measurement. Finally, a spin-decoupled metasurface combining the propagation and geometric phase is constructed, which allows simultaneous discrimination of SAM and OAM. Our proposed method may be promising for a wide range of applications in AM measurements and polarization singularity detection.